Acceleration and deceleration phases in the pull - Isaak, L.
An examination of the velocity of the bar during the pull. The mechanics of the pull. The critical height in the Snatch. What causes the bar to slow in the middle of the pull? Why are some lifters more effective in the middle of the pull?